ОСТАННІ ТЕНДЕНЦІЇ ПІДГОТОВКИ ЕКОНОМІСТІВ У ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДАХ УКРАЇНИ - Загородня, Алла (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Метою дослідження є висвітлення останніх тенденцій підготовки економістів у вищих навчальних закладах України. Автором здійснено моніторинг та проаналізовано дослідження науковців з цієї проблеми. Автор робить висновок, що процес модернізації професійної підготовки фахівців економічної галузі зорієнтований на розвиток особистості та інтеграцію в європейський світовий освітній простір. Зміна пріоритетів професійної підготовки фахівців економічної галузі та завдання створення ефективної системи ступеневої професійної підготовки визначають появу низки певних тенденцій. Целью исследования является освещение последних тенденций подготовки экономистов в высших учебных заведениях Украины. Автором осуществлен мониторинг и проанализированы исследования ученых по этой проблеме. Автор делает вывод, что процесс модернизации профессиональной подготовки специалистов экономической отрасли ориентирован на развитие личности и интеграцию в европейское мировое образовательное пространство. Изменение приоритетов профессиональной подготовки специалистов экономической отрасли и задачи создания эффективной системы многоступенчатой профессиональной подготовки определяют появление ряда определенных тенденций. The aim of the study is to highlight the latest trends economists training in higher educational institutions of Ukraine. The author has monitored and analyzed scientific studies on this issue. The author reveals the problem of the quality and content of professional training of the economic sector in Ukraine. The author notes that the requirements of social order of modern society on training specialists of economic sectors as creative individuals, capable professional and personal self-development and self-improvement to function in a changing environment professional environment, determine the relevance of renewal, reform and modernize the content of their training in terms of higher education . The author concludes that the process of modernization of professional training of the economic sector focused on personal development and integration into the European world educational space. Changing priorities professional training sector and economic task of creating an effective system of step training determine the appearance of a number of specific trends.